2022-RA-324-ESGO Phase 2 results from the LIO-1 STUDY (NCT04042116; ENGOT-GYN3/AGO/LIO): efficacy and safety of lucitanib + nivolumab in patients with advanced gynaecological malignancies. (20th October 2022) - Concin, Nicole; Patel, Manish R; Makker, Vicky; Oaknin, Ana; Pignata, Sandro; Backes, Floor J; González-Martín, Antonio; Eskander, Ramez N; Pothuri, Bhavana; Richardson, Debra L; Secord, Angeles Alvarez; van Nieuwenhuysen, Els; et al.
Abstract : Introduction/Background: LIO-1 (NCT04042116 ) assesses the combination of lucitanib, an oral anti-angiogenic, multikinase inhibitor administered using safety-based dose titration, and nivolumab, an inhibitor of programmed cell death receptor 1 (PD-1). Here, we present phase 2 study results of this combination in 4 advanced gynaecological malignancies. Methodology: LIO-1 enrolled patients with advanced, recurrent or metastatic endometrial cancer (EC), cervical cancer (CC), high-grade ovarian cancer (OC) or EC/OC with clear-cell histology (EOCC). Patients with EC, CC or EOCC received ≥1 prior platinum-based chemotherapies (CC, ± bevacizumab; EOCC, + taxane); patients with OC received ≥2 prior chemotherapies (including ≥1 platinum doublet). Patients received lucitanib at a starting dose of 6 mg QD plus intravenous nivolumab 480 mg every 28 days. Lucitanib dose could be escalated to 8 mg then 10 mg QD. The data cutoff was 14 April 2022. Results: Total treated was 124 patients; 31 (25.0%) patients are ongoing. At data cutoff, 32 (25.8%) patients escalated to lucitanib 8 mg and 20 (16.1%) to 10 mg. The confirmed best overall response rates at data cutoff were: EC cohort, 5/22 (22.7%); CC cohort, 12/46 (26.1%); OC cohort, 4/33 (12.1%); EOCC cohort, 6/23 (26.1%). Among EC-cohort patients, confirmed responses were reported for 2/5 patients who received prior PD-1 inhibitor (both were non-responders to prior PD-1 inhibitor). Among EC-cohort patients with known microsatellite status, confirmed responses were observed in 3/14 with microsatellite stability and 2/3 with high instability. Grade ≥3 treatment-emergent adverse events (TEAEs) considered study-treatment related were reported in 55 (44.4%) patients, with the most frequent being hypertension (n=30 [24.2%]). TEAEs leading to lucitanib dose reduction or discontinuation occurred in 21 (16.9%) and 20 (16.1%) patients, respectively. Conclusion: Lucitanib + nivolumab displays anti-tumour activity in patients with advanced gynaecological malignancies, including clear-cell cancer. Effective dose titration resulted in manageable safety, similar to previous reports.